Mid- to late- term follow- up of primary hip and knee arthroplasty: the UK SAFE evidence- based recommendations. (2023) - Kingsbury, S. R.; Smith, L. K. K.; Villanueva, R. Pinedo-; Judge, A.; West, R.; Wright, J. M.; Stone, M. H.; Conaghan, P. G.
No abstract available